Cancer exosomes induce tumor innervation. Issue 1 (December 2018) - Madeo, Marianna; Colbert, Paul; Vermeer, Daniel; Lucido, Christopher; Cain, Jacob; Vichaya, Elisabeth; Grossberg, Aaron; Muirhead, DesiRae; Rickel, Alex; Hong, Zhongkui; Zhao, Jing; Weimer, Jill; et al.
Abstract Patients with densely innervated tumors suffer with increased metastasis and decreased survival as compared to those with less innervated tumors. We hypothesize that in some tumors, nerves are acquired by a tumor-induced process, called axonogenesis. Here, we use PC12 cells as an in vitro neuronal model, human tumor samples and murine in vivo models to test this hypothesis. When appropriately stimulated, PC12 cells extend processes, called neurites. We show that patient tumors release vesicles, called exosomes, which induce PC12 neurite outgrowth. Using a cancer mouse model, we show that tumors compromised in exosome release are less innervated than controls. Moreover, in vivo pharmacological blockade of exosome release similarly attenuates tumor innervation. We characterize these nerves as sensory in nature and demonstrate that axonogenesis is potentiated by the exosome-packaged axonal guidance molecule, EphrinB1. These findings indicate that tumor released exosomes induce tumor innervation and exosomes containing EphrinB1 potentiate this activity. Tumors can induce axonogenesis which is commonly associated with worse outcomes. Here, the authors show that this phenomenon is mediated by cancer exosomes.